2007
DOI: 10.1093/nar/gkm627
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-dependent DNA deformability studied using molecular dynamics simulations

Abstract: Proteins recognize specific DNA sequences not only through direct contact between amino acids and bases, but also indirectly based on the sequence-dependent conformation and deformability of the DNA (indirect readout). We used molecular dynamics simulations to analyze the sequence-dependent DNA conformations of all 136 possible tetrameric sequences sandwiched between CGCG sequences. The deformability of dimeric steps obtained by the simulations is consistent with that by the crystal structures. The simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
126
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(139 citation statements)
references
References 49 publications
9
126
2
2
Order By: Relevance
“…Thus, AT and TA dinucleotides mark linker/nucleosome borders to a greater degree than found by chance, but not all or even most nucleosomes are marked in such a way. It may be relevant that TA dinucleotides impart more flexibility into DNA, and AT imparts more rigidity, than other dinucleotides (Packer et al 2000;Fujii et al 2007). Such dinucleotides, when present at selective nucleosome borders, might influence nucleosome positioning.…”
Section: Dna Sequences That Organize Nucleosomes Are Concentrated At mentioning
confidence: 99%
“…Thus, AT and TA dinucleotides mark linker/nucleosome borders to a greater degree than found by chance, but not all or even most nucleosomes are marked in such a way. It may be relevant that TA dinucleotides impart more flexibility into DNA, and AT imparts more rigidity, than other dinucleotides (Packer et al 2000;Fujii et al 2007). Such dinucleotides, when present at selective nucleosome borders, might influence nucleosome positioning.…”
Section: Dna Sequences That Organize Nucleosomes Are Concentrated At mentioning
confidence: 99%
“…Overall, the employment of force field and molecular dynamics approaches appears to provide a better representation of the experimental data to when compared to the static description provided by hybrid QM/MM approaches when compared to a static description. The flexibility and deformability of native DNA has been extensively studied, 16,25,46,49 and it is well established that both features are sequence-dependent, with base composition and the presence of specific sequences substantially contributing to the malleability of the double helix. 16,50 In the present work, the different conformations that DNA can adopt were evaluated by measuring relevant base pair parameters during our simulations.…”
Section: Wwwlandesbiosciencecommentioning
confidence: 99%
“…The flexibility and deformability of native DNA has been extensively studied, 16,25,46,49 and it is well established that both features are sequence-dependent, with base composition and the presence of specific sequences substantially contributing to the malleability of the double helix. 16,50 In the present work, the different conformations that DNA can adopt were evaluated by measuring relevant base pair parameters during our simulations. Previous work has shown that the AA/TT and GA/TC steps are considered to be the ones with less variability.…”
Section: Wwwlandesbiosciencecommentioning
confidence: 99%
See 1 more Smart Citation
“…In the human genome, 19.4 CA repeats occur per mega base pair, representing the most common simple-sequence repeat motif (Waterston et al, 2002). Among all dinucleotides, the structure of CA dinucleotides are the most stable regardless of their environment, and the stability of the DNA structure enhances the stability of the chromatin as well (Fujii et al, 2007). This stable chromatin structure allows the binding of numerous transcriptional activators and splicing regulators.…”
Section: Putative Novel Cis-regulatory Elements: (Ca)n Repeatsmentioning
confidence: 99%